Performance Study of Cemara Raya Road in Banjarmasin City Using the 2023 PKJI Method - Adhi Surya; Sulastini Sulastini; Anovan Ashari (PT. Global Research Collaboration, 2026)
This study examines the performance of Cemara Raya Road in Banjarmasin City as a representative case of urban congestion in developing contexts, where road infrastructure functions not only as a mobility corridor but also as a space for socio-economic activities. Using a mixed methods sequential explanatory design, the research integrates quantitative analysis based on the PKJI 2023 framework with qualitative insights derived from stakeholder perspectives and field observations. The findings reveal that the road operates under highly saturated conditions, with a degree of saturation ranging from 0.90 to 1.05, corresponding to Level of Service E–F, indicating unstable traffic flow and severe congestion. The study identifies side friction caused by on-street parking, street vendors, and informal loading activities as the most dominant factor reducing effective road capacity, alongside heterogeneous traffic composition dominated by motorcycles. Additionally, weak traffic management, poor infrastructure conditions, and lack of temporal regulation further exacerbate congestion. The integration of quantitative and qualitative findings highlights that congestion on Cemara Raya Road is a systemic issue resulting from the interaction of physical, behavioral, and institutional factors. The study proposes both short-term and long-term strategies, including stricter regulation, infrastructure improvement, and the implementation of intelligent traffic systems, to achieve sustainable urban mobility and improve overall road performance.